Quantitative accident consequences analysis on chemical plant of acetic acid production / Mohd Aizad Ahmad, Noranierah Noho and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Noho, Noranierah; Abdul Rashid, Zulkifli (Universiti Teknologi MARA Shah Alam, 2022)
The growing concern about the possibility of major chemical accidents in India has driven both government and industry to figure out ways to recognise and evaluate potential hazards. A Quantitative Accident Consequences Analysis is a formal and structured approach to accident analysis that quantifies the consequence associated with engineering process operations. The application of accident analysis for this study is to achieve two objectives which are to identify hazardous substances and scenarios that can occur in acetic acid plant and the consequence to people outside and inside of the plant involved estimation of the accidental consequences with threat zone distance and area affected calculation. The acetic acid production plant located at MIDC Bhosari, Pimpri Chinchwad in Maharashtra India is the subject of this study. The methodology for this study is applied calculation of chemical inventories and process piping flow, assumptions, and selections are based on plant design supported by simulation using HYSYS software; and using ALOHA and MARPLOT Software for simulation of the accidental consequences. This study has a selected wind direction from East (E), which were blowing into residential area. Methanol reactor, R-101 produced boiling liquid expanding vapor explosion (BLEVE) scenario which has the largest affected area of 572, 461 m2 and the longest distance of 427 meters, compare to other equipment in the plant.